Multi-omics insights into the role of mitophagy receptor-related genes in glioma prognosis and immune microenvironment remodeling - Xu, Yuheng; Weng, Wanqi; Xiong, Yuanyi; Hu, Jintao; Chen, Chunmei; Peng, Zhiqiang; Wang, Zhaotao (Frontiers in Immunology, 2025)
BackgroundMitophagy receptor-related genes (MRRGs) orchestrate mitochondrial quality control and may shape glioma progression and immune tolerance, yet their integrated prognostic and immunobiological significance remains unclear.MethodsWe combined WGCNA, single−cell AUCell scoring, and LASSO/Cox modeling across public glioma cohorts to derive and externally validate a 17−gene MRRG risk signature. Multi−omics comparisons (transcriptome, pathway enrichment, mutation, and GWAS association), immune infiltration, and therapy response prediction were performed. Core driver(s) were interrogated by in vitro functional assays and in vivo xenograft validation.ResultsThe MRRG signature robustly stratified overall survival across independent datasets and remained an independent prognostic factor after multivariable adjustment. High−risk tumors exhibited activation of P53 signaling and MAPK signaling pathway, coupled with immunosuppressive remodeling characterized by increased M2−like macrophage infiltration and T cell dysfunction. Integrative analyses highlighted IFNAR2 as a central node; its silencing impaired glioma cell proliferation, invasion, and metastatic potential, while in vivo suppression attenuated tumor growth. The model correlated with differential predicted sensitivity to immunotherapy and targeted agents, suggesting potential for precision stratification.ConclusionWe present and validate a 17−MRRG prognostic model that links mitophagy receptors to glioma immunosuppression and clinical outcome, and identify IFNAR2 as a functional driver. These findings provide a rationale for incorporating MRRG profiling into prognostic assessment and therapeutic decision−making in glioma.